2014
DOI: 10.1111/pcmr.12219
|View full text |Cite
|
Sign up to set email alerts
|

Type I interferon signature in the initiation of the immune response in vitiligo

Abstract: Immune-mediated responses are consistently observed in progressing vitiligo at the edge of depigmenting patches. Besides the role of the adaptive immune system, the profile of the innate immune response is now at the center of the stage. We report that plasmacytoid dendritic cells (pDC), which are the major interferon (IFN)-alpha-producing cells, are part of the infiltrate of progressive vitiligo with local production of MxA (a protein induced by IFNα). MxA was associated with expression of the type I IFN-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
101
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(118 citation statements)
references
References 51 publications
(58 reference statements)
14
101
0
3
Order By: Relevance
“…Flow cytometry of blister fluid in the screening group initially revealed that active lesional sites had a larger infiltrate of CD8 + T cells than non-lesional sites, or when compared to the skin of healthy individuals (Fig 2A and Supplementary Figure 1). We and others reported that skin-infiltrating CD8+ T cells express CXCR3, their receptor, when analyzed by IHC 4,10,21 . Here we found that CD8+ T cells uniformly express CXCR3 in the skin by flow cytometry (Fig 2B), supporting previous results.…”
Section: Resultsmentioning
confidence: 86%
“…Flow cytometry of blister fluid in the screening group initially revealed that active lesional sites had a larger infiltrate of CD8 + T cells than non-lesional sites, or when compared to the skin of healthy individuals (Fig 2A and Supplementary Figure 1). We and others reported that skin-infiltrating CD8+ T cells express CXCR3, their receptor, when analyzed by IHC 4,10,21 . Here we found that CD8+ T cells uniformly express CXCR3 in the skin by flow cytometry (Fig 2B), supporting previous results.…”
Section: Resultsmentioning
confidence: 86%
“…A similar composite gene expression profile also was predictive of favorable clinical outcome with therapeutic cancer vaccines [19,20]. A gene expression profile including a type I IFN signature has been found to have positive prognostic value in breast cancer [45-47], and also has been identified in patients undergoing the evolution of vitiligo [48]. Together, these correlative data suggested that type I IFN production might be integrally involved with adaptive T cell responses against tumor antigens.…”
Section: Mechanism Of Innate Immune Sensing Driving Spontaneous Adaptmentioning
confidence: 99%
“…The type I IFN profile has also been shown to predict favorable clinical responses to therapeutic cancer vaccines (26) and to anthracycline-based chemotherapy in patients with breast carcinoma characterized by poor prognosis (27). Infiltration of plasmacytoid dendritic cells (pDCs; a subpopulation of DCs that produces high amounts of type I IFNs) into the skin lesions of vitiligo patients generates type I IFN and thus drives the activation and recruitment of autoimmune T cells (28). Overall, the link between a type I IFN profile and T cell responses suggests that these cytokines might be involved in the generation of an adaptive T cell response against tumor antigens.…”
Section: Introductionmentioning
confidence: 99%